2016 IEEE International Conference on Imaging Systems and Techniques (IST) 2016
DOI: 10.1109/ist.2016.7738258
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral selection based algorithm for plant classification

Abstract: Abstract-The popularity of using hyperspectral imaging systems in studying and monitoring plant properties and conditions has increased lately. This increase has been driven by both financial and environmental advantages of such systems. Using a nondestructive hyperspectral imaging system improves the breeding process, increases profit, and reduces the usage of herbicide, thus reducing side effects to plants and environment. This paper is concerned with the use of hyperspectral image analysis for differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…It should be stated that no comparison between the selection algorithm and existing empirical indices (i.e. vegetation and disease) in the literature was performed since this comparison was already demonstrated in our previous work [13]. In addition, 50% of the samples were used for training with 10-fold cross validation and the remaining samples for testing in the conventional SVM classifier, while 60% of the normal samples were used for training and the remaining 40% and all the abnormal samples were used for testing and validation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be stated that no comparison between the selection algorithm and existing empirical indices (i.e. vegetation and disease) in the literature was performed since this comparison was already demonstrated in our previous work [13]. In addition, 50% of the samples were used for training with 10-fold cross validation and the remaining samples for testing in the conventional SVM classifier, while 60% of the normal samples were used for training and the remaining 40% and all the abnormal samples were used for testing and validation.…”
Section: Resultsmentioning
confidence: 99%
“…A good review of feature selection processes, models, and algorithms can be found in [11]- [13]. In short, the k-th feature (x k ) from a feature space x = {x 1 , .…”
Section: A Feature Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, researchers have shown an increased interest in developing efficient and effective analysis tools for hyperspectral images or data, since a large amount of HSI data is being generated and it is difficult, if not impossible, to analyze the information directly from the pixel values [16], [17]. Increasingly machine learning techniques are applied due to the scale and complexity of the problems.…”
Section: Introductionmentioning
confidence: 99%